Accurate and simple determination of oxcarbazepine in human plasma and urine samples using switchable‐hydrophilicity solvent in GC–MS. (25th June 2020) - Erarpat, Sezin; Bodur, Süleyman; Ayyıldız, Merve Fırat; Günkara, Ömer Tahir; Erulaş, Fatih; Chormey, Dotse Selali; Turak, Fatma; Budak, Türkan Börklü; Bakırdere, Sezgin
Abstract: This work presents a sensitive and rapid analytical method for the determination of oxcarbazepine in human plasma and urine samples. A vortex‐assisted switchable hydrophilicity solvent‐based liquid phase microextraction (VA–SHS–LPME) was used to preconcentrate oxcarbazepine from the samples before the determination by gas chromatography mass spectrometry. The switchable hydrophilicity solvent was synthesized by protonating N, N ‐dimethylbenzylamine with carbon dioxide to make it totally miscible with an equivalent volume of water. Parameters of the VA–SHS–LPME method including volume of switchable hydrophilicity solvent, concentration/volume of sodium hydroxide and vortex period were systematically optimized. Under the optimum conditions, good linearity ranging from 27.03 to 353.47 μg/kg was obtained for the analyte. Limit of detection and quantitation values were found to be 6.2 and 21 μg/kg (mass base), respectively. The relative standard deviation was calculated as 6.9% for six replicate measurements of the lowest concentration of the calibration plot. Satisfactory recovery results were calculated in the range of 97–100% for human plasma and urine samples spiked at five different concentrations.